1999
DOI: 10.1128/iai.67.4.1992-2000.1999
|View full text |Cite
|
Sign up to set email alerts
|

Segmented Filamentous Bacteria Are Potent Stimuli of a Physiologically Normal State of the Murine Gut Mucosal Immune System

Abstract: Segmented filamentous bacteria (SFB) are autochthonous bacteria inhabiting the intestinal tracts of many species, including humans. We studied the effect of SFB on the mucosal immune system by monoassociating formerly germfree C3H/HeN mice with SFB. At various time points during 190 days of colonization, fragment cultures of small intestine and Peyer’s patches (PP) were analyzed for total immunoglobulin A (IgA) and SFB-specific IgA production. Also, phenotypic changes indicating germinal center reactions (GCRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(74 citation statements)
references
References 24 publications
3
62
1
Order By: Relevance
“…Examination of the transcriptional programming induced in IECs by SFB adhesion revealed that serum amyloid A (SAA) proteins are important factors in Th17 programming . The molecular trigger of SAA following SFB adhesion was reported to include the transcription factor CCAAT/enhancer‐binding protein δ induced by reorganization of the actin skeleton in epithelial cells . Epithelial secretion of SAA1 and SAA2 induced by SFB adhesion acts on CD11c + cells to stimulate cytokine production that shapes the tissue microenvironment to potentiate the induction of Th17 cells.…”
Section: Adhesion Of Sfb To Iecs As a Crucial Factor In Shaping Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of the transcriptional programming induced in IECs by SFB adhesion revealed that serum amyloid A (SAA) proteins are important factors in Th17 programming . The molecular trigger of SAA following SFB adhesion was reported to include the transcription factor CCAAT/enhancer‐binding protein δ induced by reorganization of the actin skeleton in epithelial cells . Epithelial secretion of SAA1 and SAA2 induced by SFB adhesion acts on CD11c + cells to stimulate cytokine production that shapes the tissue microenvironment to potentiate the induction of Th17 cells.…”
Section: Adhesion Of Sfb To Iecs As a Crucial Factor In Shaping Immunitymentioning
confidence: 99%
“…Epithelial secretion of SAA1 and SAA2 induced by SFB adhesion acts on CD11c + cells to stimulate cytokine production that shapes the tissue microenvironment to potentiate the induction of Th17 cells. Interleukin‐23 produced by antigen‐presenting cells (APCs) upon recognition of SFB also initiates an IL‐23R/IL‐22 circuit in type 3 ILCs (ILC3) to promote SAA secretion from the epithelium; however, this appears to occur independent of SFB adhesion …”
Section: Adhesion Of Sfb To Iecs As a Crucial Factor In Shaping Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…In SFB‐monoassociated mice, the immunological characteristics of the small intestine are almost converted to that in conventional mice without the assistance of other bacteria (Umesaki et al ., ). GF mice, after being solely colonized with SFB, show fully developed thymus‐dependent IELs with an increase in IgA‐producing cells and IgA titers (Klaasen et al ., , b; Umesaki et al ., , ; Snel et al ., ; Talham et al ., ). These results indicate that SFB could stimulate the mucosal immune system to a greater extent than other autochthonous gut bacteria (Klaasen et al ., , b).…”
Section: Introductionmentioning
confidence: 97%
“…mediated by antibodies produced by B cells) to recognize cells and tag pathogenic invaders for destruction, and IgA‐secreting cells are significantly reduced in germ‐free animals and absent in neonates (Benveniste et al, ,; Macpherson et al, ). Only colonization with specifically‐selected bacteria during a window of host development provokes the complete restoration of immune activity (Talham et al, ; Round and Mazmanian, ). These interactions are important for promoting immune development, decreasing the risk of autoimmune diseases, and establishing host tolerance of the gut microbiota.…”
Section: General Host‐gut Microbe Interactionsmentioning
confidence: 99%